Primerjava digitalnega modela reliefa (DMR), senčenega z monokromatsko svetlobo iz stacionarnega vira in multispektralno senčenega DMR iz več smeri na območju Slovenije - Komac, Marko (Geologija, 2000)
Until recently only the experienced cartographers manually shaded the relief on maps and images. Only the computer technology enabled automatic hillshadingof the relief and for this purpose the classical method of a distant, single-source white light was adopted. The image produced is drawn in grey scale. This method however does not produce the best image possible, since there are always parts of the image that are shaded with very dark tonesand the structures of the relief are not clearly visible, if they are visible at all. Hence, a new method was developed that uses the colour composite techniqueof the three images, shaded from different point of view (azimuth angle). Each of the three images represents one of the basic colours of the RGB colour model. The method brings promising results because it successfully deals with some problems that arise with classical hillshading. The article successfully transfers the method onto Slovenian "soils".
Keywords: digitalni model reliefa; geodesy; geodezija; kartografija; relief; satelitski posnetki; Slovenia; Slovenija; topography